El bajo autoestima en las niñas y niños y su incidencias en el proceso enseñanza aprendizaje del primer año de educación básica de la escuela María Montessori de la parroquia Tenguel de la provincia del Guayas en el periodo lectivo 2012 - 2013. - Solórzano Barberan, Genith María (2013)
To conduct the research, proposed objectives according to the variable presented. Identify the factors that influence home in the formation and development of low self-esteem of children in the first year of basic education, 2. Define how low self-esteem affects children in the first year of basic education in the process teaching and learning, 3. Determine the teaching activities applied in the classroom to help children in the first year of basic education to overcome the problem of low self-esteem, 4. Propose mediantes workshops to develop teaching strategies esteem each child with individualized teaching style, which allowed the specific objectives comply with the investigation. The investigation pursuant to nature and is essentially descriptive characteristics and features in the literature assumes as theoretical framework is based on recognized and prestigious authors. Furthermore, it is documentary that analyzes the characteristics, historical development and current status of the selected educational institution. But research will mainly field as guides survey, interview and observation guide the social actors involved in the problem under study were applied, we rely on the scientific method, descriptive method, and hypothetical-deductive, in As techniques apply the technique of the survey and literature. As shown take 8 teachers and 66 parents from the first year of basic education the Fiscal school Montessori with the investigation, it is provided with a proposal to mobilize the classroom to reinforce the knowledge of teachers and to raise esteem to children in the first year of basic education also that the conclusions they arrive, a starting point for future research on the subject is constituted.